A proof-of-concept study of a novel ventilation heat recovery vapour injection air source heat pump. (15th March 2022) - Fan, Yi; Li, Jing; Zhao, Xudong; Myers, Steve; Cheng, Yuanda; Yu, Min; Golizadeh Akhlaghi, Yousef; Ma, Xiaoli; Yu, Sen
Highlights: A proof-of-concept heat pump prototype was developed. The performance under various working conditions was tested. The efficiency was 3.81 at cold and hot side temperatures of −10 °C and 35 °C. The defrosting process using exhaust air was fast with minor power consumption. The Technical feasibility of the novel heat pump was preliminarily demonstrated. Abstract: Conventional air source heat pumps suffer from frosting in winter and consume a large amount of electricity for defrosting. Meanwhile, ventilation heat recovery is an important approach to energy saving in buildings. This paper conducts a proof-of-concept study of a novel ventilation heat recovery vapour injection air source heat pump. A prototype is built and tested. It has a unique defrosting process driven by the warm exhaust air from buildings. In the normal operation, the exhaust air is first cooled down by a medium-pressure evaporator. It is then mixed with the ambient air to heat the low-pressure evaporator. Both theoretical simulation and experimental validation are carried out. The results show that the proposed heat pump can significantly decrease the thermodynamic irreversibility and electricity consumption, thus leading to a higher efficiency. For the novel heat pump, the coefficient of performance increased from 3.8 to 4.5 when the ambient temperature varied from −5°C to 10 °C. Furthermore, the defrosting process using exhaust air is fast and efficient. The defrosting duration (within 4 mins) is less than 30% of the frosting period at 0 °C, with little power consumption. Consequently, the prototype has demonstrated an enhanced performance with high flexibility and feasibility. It tackles the challenges of conventional air source heat pumps and is promising in the cold climate area application.